Linking Public Service Availability to Village Welfare - Pauline Gaspersz (The Journal of Indonesia Sustainable Development Planning, 2023)
This study aims to provide a village-level analysis explaining the link between the availability of essential services and welfare, which is scarce in this study area. The accessibility of state-provided facilities is related to poverty reduction. On the other hand, the village, the lowest administrative level in Indonesia, is entrusted with a particular delegation of authority and budget. Therefore, the efficient management of delegated authority and budget at the village-level should be reflected in good infrastructure. By employing logistic regression, this study examines the relationship between the village development's status as a proxy for people's welfare and the availability of essential services in Maluku and Maluku Utara, two neighboring provinces with significant differences in poverty rates. The main finding of this research is that infrastructure plays an important role in improving people's welfare at the village level. In addition, surprisingly, crimes contribute to the village's development.